PERBEDAAN GANGGUAN KOGNITIF SUBJEK STROKE ISKEMIK BERDASARKAN SISI HEMIPARESIS - Gabriella,* Budi Riyanto Wreksoatmodjo,** Andre** (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION COGNITIVE IMPAIRMENT IN STROKE HAS A SIGNIFICANT IMPACT ON THE QUALITY OF LIFE AND IS DIFFERENT FROM THE LOCATION OF THE LESION PATIENTS WITH A LESION IN THE LEFT CEREBRAL HEMISPHERE TEND TO HAVE COGNITIVE IMPAIRMENT AND DEMENTIA